Social integration: Institutions and actors - Marshall Wolfe (United Nations Research Institute for Social Development (UNRISD), 1994)
In policy-oriented discourse, social integration means different things to different participants and cannot simply be regarded as an end to be maximized or prescribed for. The policy-relevant question is not how to increase integration per se, but how to distinguish patterns of integration conducive to more equitable and creative societies. The term "social integration" invites analysis of the concrete networks of relations and institutions that support or undermine the livelihood of people in given times and places. The processes of social integration, disintegration and reintegration work themselves out through a wide range of organizations and other structured arrangements or "institutions" from the international level to that of the family. These institutions embody traditions, rules and expectations; they can bestow on people complementary or alternative social identities. An equally wide range of social actors try to make use of these institutions for purposes of self-protection and advancement, and for stabilization, reform or transformation of the system.
Keywords: 330